Impact of different sources of credit in creating extreme farmer distress in India. Issue 6 (5th August 2019) - Pandey, Bhavna; Bandyopadhyay, Prabir; Guiette, Alain
Abstract : Purpose: According to the published report by the National Sample Survey 2014 the data says that the incidence of indebtedness among households in the rural areas of Maharashtra, India, is almost twice that of other rural places in India. Around 64 percent of rural households are indebted in Maharashtra as against 31 percent other households in India. The purpose of this paper is to examine which source of credit is creating more distress among the farmers. Further the researchers also wanted to find out the reasons why the farmers choose private moneylender over the formal financial institutions. Design/methodology/approach: To achieve the objective, the authors used the mixed method methodology. The qualitative study was done using the ethnography approach .In depth interviews were conducted and coded accordingly to find out the themes. The interviews conducted were semi structured and had open ended questions in it, followed by a structured questionnaire. Different statistical tests were also applied on the responses obtained from the questionnaire to check the reliability and validity of the interviews. This methodology gave a robustness to the findings of the study. Findings: The results show that sources of loan play a major role in causing farmer distress in Maharashtra. The findings also show major reasons like grapevine bureaucracy, lengthy documentation, etc. as the major reasons for choosing private lenders over the formal financial institutions. The most interesting finding of the study was a phenomena observed during the field study. The borrowers first borrow from financial institutions for their credit needs, when they fail to repay the debt borrowed they again borrow money from the private money lenders and with this borrowed money they try repaying a part of the old existing loan in order to make themselves eligible for the next loan cycle. Research limitations/implications: The limitation of the study is that due to time constraint only two districts with high number of farmer suicide could be visited. Given more time and fund a comparative study can be done among different states of India. Practical implications: This study will help the policy makers in identifying the real cause of farmer distress. The motive behind the policies made by the government is very noble but the implementation of these policies is inadequate and without a strong research base. The paper will be able to highlight how much the state intervention is required at multiple levels in order to ensure that the benefits reaches to those who deserve it. Social implications: It is imperative that we have yet not realized the gravity of the situation where people belonging from a community which is so essential to the economy are killing themselves because of lack of money. This is not just about the fact that the people who give us food are unable to access food themselves. Originality/value: The paper contains significant information with regard to indebtedness. It focuses on the issue troubling the authorities the most. It provides the ground realities of the incidence of indebtedness in Maharashtra, one of the most distressed states of India. Lot of studies have been done in the past but very few studies have used mixed methodology to study this incidence of debt among the farmers of Maharashtra. This study also unveils a new phenomena of borrowing happening among the farmers of Maharashtra.